Interleukin-38 overexpression in keratinocytes limits desquamation but does not affect the global severity of imiquimod-induced skin inflammation in mice - Huard, Arnaud; Rodriguez, Emiliana; Talabot-Ayer, Dominique; Weigert, Andreas; Palmer, Gaby (Frontiers in Immunology, 2024)
Psoriasis is a common chronic inflammatory skin disease that significantly impacts the patients’ quality of life. Recent studies highlighted the function of the interleukin (IL)-1 family member IL-38 in skin homeostasis and suggested an anti-inflammatory role for this cytokine in psoriasis. In this study, we generated mice specifically overexpressing the IL-38 protein in epidermal keratinocytes. We confirmed IL-38 overexpression in the skin by Western blotting. We further detected the protein by ELISA in the plasma, as well as in conditioned media of skin explants isolated from IL-38 overexpressing mice, indicating that IL-38 produced in the epidermis is released from keratinocytes and can be found in the circulation. Unexpectedly, epidermal IL-38 overexpression did not impact the global severity of imiquimod (IMQ)-induced skin inflammation, Similarly, keratinocyte activation and differentiation in IMQ-treated skin were not affected by increased IL-38 expression and there was no global effect on local or systemic inflammatory responses. Nevertheless, we observed a selective inhibition of CXCL1 and IL-6 production in response to IMQ in IL-38 overexpressing skin, as well as reduced Ly6g mRNA levels, suggesting decreased neutrophil infiltration. Epidermal IL-38 overexpression also selectively affected the desquamation process during IMQ-induced psoriasis, as illustrated by reduced plaque formation. Taken together, our results validate the generation of a new mouse line allowing for tissue-specific IL-38 overexpression. Interestingly, epidermal IL-38 overexpression selectively affected specific disease-associated readouts during IMQ-induced psoriasis, suggesting a more complex role of IL-38 in the inflamed skin than previously recognized. In particular, our data highlight a potential involvement of IL-38 in the regulation of skin desquamation.